2019
DOI: 10.1016/j.jaci.2018.07.040
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco smoke as a risk factor for allergic sensitization in adults: Conclusions of a systematic review and meta-analysis

Abstract: Allergic sensitization to aeroallergens is a common phenomenon and a crucial step in the development of allergic diseases. Nonetheless, the influence of tobacco smoke exposure on the development of allergic sensitization in adults is quite complex and not totally understood. Therefore, our objective was to systematically review the existing evidence regarding this topic and to perform a metaanalysis of the data collected from the included studies. The search for studies that potentially matched the inclusion c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Many previous reports have revealed that CS could augment allergic inflammation (Botelho et al, 2011;Saulyte et al, 2014;Strzelak et al, 2018); however, chronic smoking exerts a protective effect on allergic sensitization to some aeroallergens and prevents allergic diseases protecting against pollinosis (Hjern et al, 2001;Sopori, 2002;Nagata et al, 2008;Monico et al, 2019). Various components of CS suppress the Th2 cell response, which plays an important role in IgE production and in the development of immediate hypersensitivity (Ozaki et al, 2010), although the mechanism by which CS protects against allergic sensitization has not been well clarified.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many previous reports have revealed that CS could augment allergic inflammation (Botelho et al, 2011;Saulyte et al, 2014;Strzelak et al, 2018); however, chronic smoking exerts a protective effect on allergic sensitization to some aeroallergens and prevents allergic diseases protecting against pollinosis (Hjern et al, 2001;Sopori, 2002;Nagata et al, 2008;Monico et al, 2019). Various components of CS suppress the Th2 cell response, which plays an important role in IgE production and in the development of immediate hypersensitivity (Ozaki et al, 2010), although the mechanism by which CS protects against allergic sensitization has not been well clarified.…”
Section: Discussionmentioning
confidence: 99%
“…Allergy is a predisposing factor for multiple respiratory conditions including allergic rhinitis and asthma (Gelber et al, 1993;Monico et al, 2019). Cigarette smoke (CS) is a risk factor of developing allergic diseases, mediated by excessive immune responses to various allergens, and impacts the immune system (Mehta et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Current smoking is associated with elevated total IgE antibody levels in the general population, 150 whereas most studies in asthma have found that total IgE levels are J o u r n a l P r e -p r o o f 22 not influenced by smoking status. 7,21 Smoking is associated with a reduced sensitization to common aeroallergens, 151 except for increased sensitization house dust mites in some studies. 21,151…”
Section: T2 Eosinophilic Inflammation Statusmentioning
confidence: 99%
“…7,21 Smoking is associated with a reduced sensitization to common aeroallergens, 151 except for increased sensitization house dust mites in some studies. 21,151…”
Section: T2 Eosinophilic Inflammation Statusmentioning
confidence: 99%
“…Current smoking is associated with elevated total IgE antibody levels in the general population, 151 whereas most studies in asthma have found that total IgE levels are not influenced by smoking status. 7,21 Smoking is associated with a reduced sensitization to common aeroallergens, 152 except for increased sensitization house dust mites in some studies. 21,152 T2-high eosinophilic inflammation.…”
Section: T2 Eosinophilic Inflammation Statusmentioning
confidence: 99%